2011
DOI: 10.1080/15427951.2010.558402
|View full text |Cite
|
Sign up to set email alerts
|

Defining Essential Fish Habitat for Atka Mackerel with Respect to Feeding within and Adjacent to Aleutian Islands Trawl Exclusion Zones

Abstract: The distribution patterns of Atka mackerel Pleurogrammus monopterygius were examined, both seasonally and spatially, to identify essential feeding habitat and to add to existing knowledge of diet composition. The study focused on two local aggregations in the Aleutian Islands, Alaska: one at Seguam Pass and one near Amchitka Island. At each locale, we examined the mean stomach fullness (i.e., feeding intensity) and diet composition of randomly selected fish within and outside of trawl exclusion zones (TEZs). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Hexagrammids may prefer to forage in the transition zones between stratified and mixed waters in the straits between islands (Rand & Lowe, ). While kelp greenling (shallow, rocky coastal habitat) and Atka mackerel (<200 m, rocky habitats with strong tidal currents) are widely distributed in Alaska and are generally considered coastal or nearshore species, they are particularly abundant in the western Aleutians (Logerwell et al., ), where adults feed heavily on oceanic prey such as squid, calanoid copepods, and myctophids (Barbeaux et al., ; Mecklenburg et al., ; Rand & Lowe, ). Squid and myctophids may gather along current boundaries or shelf‐edge transition zones between shelf and oceanic waters (Sinclair & Stabeno, ).…”
Section: Discussionmentioning
confidence: 99%
“…Hexagrammids may prefer to forage in the transition zones between stratified and mixed waters in the straits between islands (Rand & Lowe, ). While kelp greenling (shallow, rocky coastal habitat) and Atka mackerel (<200 m, rocky habitats with strong tidal currents) are widely distributed in Alaska and are generally considered coastal or nearshore species, they are particularly abundant in the western Aleutians (Logerwell et al., ), where adults feed heavily on oceanic prey such as squid, calanoid copepods, and myctophids (Barbeaux et al., ; Mecklenburg et al., ; Rand & Lowe, ). Squid and myctophids may gather along current boundaries or shelf‐edge transition zones between shelf and oceanic waters (Sinclair & Stabeno, ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of Atka mackerel CPUE differences might be explained by oceanographic and habitat differences of study areas and by the MPA size (i.e., 10 vs. 20 nmi). At Seguam Pass, for example, the MPA boundary is 20 nmi and happens to contain a well-documented frontal region characterized by upwelling and stratifi ed water (Coyle, 2005;Mordy et al, 2005) This area may favor feeding (Rand and Lowe, 2011) and reproduction (Cooper and McDermott, 2011). The population of Atka mackerel inside the MPA is separated from the outside population by an area of low Atka mackerel abundance which forms a natural boundary.…”
Section: Steller Sea Lion Trawl Exclusion Zonesmentioning
confidence: 99%
“…Mounting evidence indicates that the presence of sponges and corals enhances structural heterogeneity in otherwise low-relief environments and can lead to increases in biodiversity and abundance of associated animals (e.g., Tissot et al, 2006; Beazley et al., 2013; Knudby et al, 2013). The morphological features of these biogenic structures may also serve as refugia for different life stages of commercially harvested species of Sebastes (Freese and Wing, 2003;Rooper and Boldt, 2005; Baillon et al, 2012) and Atka mackerel (Pleurogrammus monopterygius) (Rand and Lowe, 2011) in Alaska waters.Previous studies have also shown putative associations of rockfishes with sponge, coral, and bryozoan assemblages across a wide range of physical and oceanographic conditions (Love et al, 1991;Rooper and Martin, 2012 to concentrate near the few boulders or rocky outcrops with attached epibenthic invertebrate communities (e.g., Freese and Wing, 2003; Du Preez and Tunnicliffe, 2011). The Pacific ocean perch has been the focus of several previous studies in Alaska, and there is strong evidence that postsettlement juveniles and adults of Pacific ocean perch are found associated with sponges and corals (Krieger, 1993; Brodeur, 2001;Rooper and Boldt, 2005;Rooper et al, 2007).…”
mentioning
confidence: 99%
“…Mounting evidence indicates that the presence of sponges and corals enhances structural heterogeneity in otherwise low-relief environments and can lead to increases in biodiversity and abundance of associated animals (e.g., Tissot et al, 2006; Beazley et al., 2013; Knudby et al, 2013). The morphological features of these biogenic structures may also serve as refugia for different life stages of commercially harvested species of Sebastes (Freese and Wing, 2003;Rooper and Boldt, 2005; Baillon et al, 2012) and Atka mackerel (Pleurogrammus monopterygius) (Rand and Lowe, 2011) in Alaska waters.…”
mentioning
confidence: 99%